Assessment of aerobic fitness and repeated sprint ability in elite male soccer: a systematic review of test protocols used in practice and research - Asimakidis, N. D.; Bishop, C.; Beato, M.; Turner, A. N. (Sports Medicine, 2025)
Background: Soccer requires players to cover distances around 10-12 km, with numerous consecutive sprints throughout the 90-min game. As such, aerobic fitness and repeated sprint ability (RSA) are crucial physical qualities for the modern soccer player to cope with the demands of the game. However, a comprehensive and systematic search of aerobic fitness and RSA assessment procedures in elite soccer has yet to be conducted. Objectives: The aims of this systematic review were to (1) identify the tests and outcome variables used to assess aerobic fitness and RSA of elite male soccer players, (2) provide normative values for the most common tests of aerobic fitness and RSA across different playing levels, and (3) report the reliability values of these aerobic fitness and RSA tests. Methods: A systematic review of the academic databases MEDLINE, CINAHL, SPORTDiscus, Web of Science, and OVID for studies published until August 2023 was conducted, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were eligible for inclusion if (1) they were original research studies, published in a peer-reviewed journal, and written in English language; (2) they had the primary aim of assessing aerobic fitness and/or RSA; (3) players were male and older than 17 years of age (i.e. mean age of the group); and (4) their playing level was defined as `professional`, `international`, or `elite`. Results: For aerobic fitness testing, 124 studies and 35 different tests were identified. Of those, 26 tests (74%) were field-based, whereas only nine (26%) were laboratory-based tests. The incremental treadmill test to exhaustion was the most commonly used aerobic fitness assessment method (56 studies, 45%), with maximal oxygen consumption (O2max) (mL/kg/min) being the most prevalent outcome variable (49 studies, 87%). The YYIR1 and YYIR2 were also commonly used tests, identified in 22 (18%) and ten studies (8%), respectively. The most frequently reported outcome variable in both tests was distance in metres, reported in 20 studies (91%) for YYIR1 and in all ten studies (100%) for YYIR2. For RSA testing, 27 studies and 18 different tests were identified. Substantial variability in the identified RSA testing protocols was observed in terms of direction (linear vs. multidirectional), sprint repetitions (6-15), sprint distance (20-40 m), type of recovery (active vs. passive), and recovery duration (10-30 s). The 6 × 40-m shuttle sprint protocol with a 180° change of direction and 20 s passive recovery was the most common RSA test, employed in eight studies (29%). Conclusions: This systematic review provides a comprehensive overview of the testing methods used to assess aerobic fitness and RSA in elite male soccer players. A total of 35 different aerobic fitness tests and 18 RSA tests were identified, highlighting the diversity in methodologies used. The most prevalent aerobic test was the incremental treadmill testing to exhaustion, with a median O2max value of 58 mL/kg/min. Field-based tests were preferred due to their practicality, cost-efficiency, and ability to assess multiple athletes simultaneously. A substantial variability in RSA testing protocols was identified in terms of sprint directions, distances, repetitions, and recovery types. Future research should focus on establishing the diagnostic accuracy of the most commonly used aerobic fitness tests to inform their utility in practice and bridge the gap between current testing practices and optimal fitness evaluation.